Book Review: Steve Keen: The New Economics: A Manifesto, Polity Press, Cambridge, UK, 2021 - Shimshon Bichler; Jonathan Nitzan (Real-World Economics Review, 2022)
Steve Keen's book, The New Economics: A Manifesto (2021), offers a new path for economics, and for good reason. In his view, neoclassicism, the paradigm that rules modern-day economics, has become a serious menace: "I regard Neoclassical economics as not merely a bad methodology for economic analysis, but as an existential threat to the continued existence of capitalism - and human civilization in general. It has to go. (155). " Strong words? Of course, but they are wholly warranted. Neoclassical economics is the official scientific underpinning of capitalism as well as its main ideological defence, and according to Keen, it fails in both tasks.2 Contrary to received opinion, neoclassicism cannot explain capitalism - either in detail or in the aggregate - and the policies it prescribes do not support but undermine the very system it defends. It must be scrapped, says Keen, and the purpose of his book is to explain why and outline what should come in its stead. Half a century worth of research and writing on the subject has made Keen one of the world's foremost critics of neoclassical economics. His previous bestseller, the rigorous-yet-accessible Debunking Economics (2011), dismantled neoclassical microeconomics. His new volume hammers its macro framework. The book focuses on three key issues: (1) the bizarre neoclassical perspective that money, credit and debt do not matter for the macroeconomy; (2) the neoclassical insistence that the economy's complex, nonlinear turbulences are best explained in linear, self-equilibrating terms; and (3) the fact that neoclassicists have hijacked the economics of climate change, using patently false assumptions to justify do-nothing policies with untold future consequences.
Keywords: P16; E4; G21; E61; G01; G; E13; Q54; 330; banks; climate; complex systems; credit; debt; finance; macroeconmics; money; neoclassical economics; policy